Paddle wheel monitor for shrimp farming increasing potential: Universiti Utara Malaysia has come up with a system that can help boost aquaculture productivity - Abu Bakar, Azlan (New Straits Times, 2013)
Aquaculture is recognised as the fastest expanding sector of food production.Asia alone produces over 80 percent of all aquaculture products and is becoming the dominant region for aquaculture.Universiti Utara Malaysia (UUM) researcher Dr Mohd Syazwan Abdullah said the shrimp-farming development is influenced by four principal factors, namely, water,land, shrimpculture technologies and human resources. Each represents a unity that can not be separated.Application of cultivation technology will need to be supported by an existence of adequate facilities and infrastructure.